2021
DOI: 10.1186/s42825-021-00060-5
|View full text |Cite
|
Sign up to set email alerts
|

Collagen fiber membrane-derived chemically and mechanically durable superhydrophobic membrane for high-performance emulsion separation

Abstract: Developing high-performance separation membrane with good durability is a highly desired while challenging issue. Herein, we reported the successful fabrication of chemically and mechanically durable superhydrophobic membrane that was prepared by embedding UiO-66 as size-sieving sites within the supramolecular fiber structure of collagen fiber membrane (CFM), followed by the polydimethylsiloxane (PDMS) coating. The as-prepared CFM/UiO-66(12)/PDMS membrane featured capillary effect-enhanced separation flux and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…, temperature, pressure, and heating). 6–8 Biomimicking the sensory functionality of skin has been investigated extensively. 9–13 A variety of electronic skins (e-skins) have been developed based on different sensing strategies ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…, temperature, pressure, and heating). 6–8 Biomimicking the sensory functionality of skin has been investigated extensively. 9–13 A variety of electronic skins (e-skins) have been developed based on different sensing strategies ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This corrosive oily wastewater is difficult to separate by conventional polymeric separation materials due to their poor resistance to acid/alkali corrosion and oil corrosion, which makes it difficult for these materials to maintain structural stability that is critical for accomplishing emulsion separation 6,7 . As a result, there is an urgent need to explore corrosive‐resistant separation materials that are capable of separating corrosive emulsions with high separation effectiveness 1,8 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 As a result, there is an urgent need to explore corrosive-resistant separation materials that are capable of separating corrosive emulsions with high separation effectiveness. 1,8 Biochars are chemically stable and have a high resistance to acidic and alkali solutions, so they are promising substrates for developing low-cost and corrosive-resistant separation materials. 9 In general, biochars are conveniently prepared by the pyrolysis of biomass at high temperatures 10 and they feature unique structural properties, such as well-developed porous structure, high specific surface area, and abundant active functional groups, thus providing accessible active sites for achieving desired separation purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-assembly abilities of collagenous materials therefore provide TSWs with another attractive opportunity to further enhance the sensitivity and sensory range, especially for the large scale deformations occurring in the microscale range triggered by high pressure stimuli. Our previous research studies have demonstrated that collagen fibers are highly reactive biopolymers rich in multiple functional groups, [10][11][12] which therefore allowed for the efficient tuning of the conductivity of TSWs via different covalent and/or no covalent reactions.…”
Section: Introductionmentioning
confidence: 99%